Vanadium Selenide Nanobelt Electrocatalyst for Dopamine-Selective Detection - Chae, Sudong; Woo, Chaeheon; Gu, Geun Ho; Kim, Tae Yeong; Jeon, Jiho; Kwon, Hyeok Jin; Oh, Seungbae; Choi, Kyung Hwan; Dong, Xue; Ahn, Jungyoon; Asghar, Ghulam; Oh, Hyung Suk; et al. (ACS Applied Nano Materials, 2023)
Electrochemical dopamine (DA) detection has been extensively studied for the practical diagnosis of neurological disorders. A major challenge in this system is to synthesize selective and sensitive DA-sensing electrocatalysts in extracellular fluids because critical interferents such as uric acid (UA) and ascorbic acid (AA) exhibit oxidation potentials similar to that of DA. Herein, we report an extremely selective and sensitive electrocatalyst for DA sensing prepared by vanadium selenide (V2Se9). A solution-based process for the first time was introduced to synthesize V2Se9, showing unique DA-philic characteristic caused by exposure of negative charge of crystal Se. Owing to its distinctive features, the prepared V2Se9 electrode detected only DA in the presence of concentrated interferents. Electrochemical characterization and computing simulation provide strong evidence that the extreme DA selectivity stems from close physical affinity between Se and DA, leading to the outer sphere electron-transfer mechanism. This is totally different from the common catechol-based oxidation process. Furthermore, the nanostructured V2Se9 electrode extremely improves DA-sensing ability as low as practical detection limit along with maintaining the inactive interferent characteristic. More interestingly, an identical unique DA-sensing ability was also observed in a V2Se9 analogue─Nb2Se9. We believe that this finding provides insights into the effect of analyte-philic properties of electrode materials on the electrocatalytic response for selective analyte quantification.
Keywords: 1d van der waal material; Analytes; Colloidal synthesis; Dopamine; Dopamine sensing; Electrochemical sensing; Interferents; Selective detection; Sensing abilities; Van der Waal; 1D van der Waals materials; colloidal synthesis; dopamine sensing; electrochemical sensing; vanadium selenide